2014
DOI: 10.1186/2052-336x-12-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pesticide residues in surface water and ground water of agriculture intensive areas

Abstract: The organochlorines (OClPs) and organophosphates (OPPs) pesticides in surface and ground water having intensive agriculture activity were investigated to evaluate their potential pollution and risks on human health. As per USEPA 8081 B method, liquid-liquid extraction followed by Gas-Chromatographic technique with electron capture detector and mass selective detector (GC-MS) were used for monitoring of pesticides. Among organochlorines, α,β,γ,δ HCH’s, aldrin, dicofol, DDT and its derivatives, α,β endosulphan’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(55 citation statements)
references
References 7 publications
1
42
2
Order By: Relevance
“…The current study, when compared with values from studies conducted on other water bodies with agricultural activities along them generally indicates that whereas the recess concentration levels of OCP pesticides in the river Afram are lower, those of the flood regimes are higher (Table 5). This is true both for local studies by [9][10][11][12][13] as well as for studies from other regions carried out by [14][15][16][17]. However, OCP residues from Densu River [18] in Ghana were about 3 folds higher than the flood concentration from the current studies.…”
Section: Resultscontrasting
confidence: 42%
“…The current study, when compared with values from studies conducted on other water bodies with agricultural activities along them generally indicates that whereas the recess concentration levels of OCP pesticides in the river Afram are lower, those of the flood regimes are higher (Table 5). This is true both for local studies by [9][10][11][12][13] as well as for studies from other regions carried out by [14][15][16][17]. However, OCP residues from Densu River [18] in Ghana were about 3 folds higher than the flood concentration from the current studies.…”
Section: Resultscontrasting
confidence: 42%
“…In the case of the Hisar district, the values were 78.5 ng/l, 115.9 ng/l, and 53 ng/l, respectively (Kaushik et al, 2012). Lari et al (2014) analyzed OCPs in the surface water and groundwater from Maharastra India (West India). They found surface water to be more highly contaminated with OCPs than groundwater.…”
Section: Persistent Organic Pesticide Levels In Watermentioning
confidence: 99%
“…Persistent organic pesticide residues have been broadly distributed in Indian soil (Al-Wabel et al, 2011;Devi et al, 2013;Hoai et al, 2010;Kata et al, in press;Kumar et al, 2014;Kumari et al, 2008;Liu et al, 2009;Senthilkumar et al, 2009), water (Huang et al, 2013;Lari et al, 2014;Malik et al, 2009;Mutiyar et al, 2011;Mutiyar and Mittal, 2012;Singh et al, 2012), air (Chakraborty et al, 2010;Devi et al, 2011;Huang et al, 2013;Srimural et al, in press;Syed et al, 2013;Zhang et al, 2008), living creatures (Bhuvaneshwari and Rajendran, 2012;Devanathan et al, 2009;Subramaniam and Solomon, 2006), and crops (Bajpai et al, 2007;Chowdhury et al, 2011). The fate of OCPs in soils in the areas of land use and cropping patterns has also been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are in line with an earlier study by Hossain et al (2015) in the sense that they found a similar maximum chlorpyrifos concentration (9.31 µg/L) in lake water in Bangladesh. Most earlier studies from different sub-(tropical) countries, however, reported lower concentrations of chlorpyrifos than our study (Leong et al, 2007;Rahmanikhah et al, 2011;Chowdhury et al, 2012a;Lari et al, 2014;Dahshan et al, 2016;Wee and Aris, 2017). Abdel-Halim et al (2006), however, reported the highest chlorpyrifos concentration as 303.8 µg/L in water samples collected from New Damietta drainage canal in Egypt, which is about 33 folds higher than our study.…”
Section: Physico-chemical Variables Of Water and Sedimentcontrasting
confidence: 55%